Regulation of Legal Interpretation - Núñez Vaquero, Álvaro (EUNOMÍA. Revista en Cultura de la Legalidad, 2016)
This paper aims to make a brief presentation of the different ways in which legal interpretation can be regulated. It begins with a brief discussion about (1) the interpretation regulation character. Next, (2) the general regulation of the interpretation methods, (3) legal definitions, (4) interpretive statutes, (5) jurisprudence and precedent, and (6) non-adjudicatory binding statements from courts are analyzed.doi: http://dx.doi.org/10.20318/eunomia.2016.3286